Про датування Бердянського кургану (за керамічними матеріалами) - Полін, С.В.; Ковальов, М.В.; Чередніченко, М.М. (Археологія, 2000)
У науковий обіг вводиться унікальний для Скіфії набір грецької кераміки початку IV ст. до н. е., знайдений у скіфському «царському» кургані біля Бердянська Запорізької області, на основі якого визначається датування кургану — кінець першої — початок другої чверті IV ст. до н. е. та поширення аналогічних керамічних виробів у межах Причорноморської Скіфії. В статье описывается и анализируется уникальный для Скифии набор греческой керамики, найденный в скифском «царском» кургане возле Бердянска Запорожской области. Он состоит из 19 остродонных амфор фасосского производства (12 из них имеют клейма), краснофигурного кратера, 4 краснофигурных и чернолакового скифосов. Дата керамического комплекса по современным данным определяется концом первой — началом второй четверги IV в. до н. э. Эта дата фиксирует время сооружения Бердянского кургана. Вероятно, в будущем, в процессе уточнения хронологии фасосских клейм станет возможным некоторое удревнение общей даты в пределах первой четверти IV в. до н. э. The paper presents the description and analysis of the unique complex of Greek ceramics from the Scythian «Tzar» burial-mound located near Berdyansk (Zaporizhzhya region). It consists of nineteen pointed amphoras (of them, twelve amphoras have trademarks) produced on Fassos, one light-on-dark crater, four light-on-dark scythoses, and one black-patent scythos. According to modem data, the complex can be dated to the end of the first quarter / the beginning of the second quarter of the 4th century BC. The date shows the period within which the Berdyansk burial-mound was constructed. This date may be subjected to refinement (back to the first quarter of the 4th cent.) when the analysis of Fassos trademarks will be completed.